PRAKTIK PEMBERIAN UPAH PEMELIHARAAN SAPI DI DUSUN BEJI JOGOROTO JOMBANG MENURUT HUKUM BISNIS SYARI’AH - Robbytul Umam; Syai’in Syai’in (JURNAL ILMIAH NUSANTARA, 2024)
This article discusses the practice of providing wages for keeping cattle in Beji hamlet, Sawiji village, Jogoroto sub-district, Jombang district, from the perspective of sharia business law. General business activities based on financial jurisprudence are commonly referred to as tijarah (trade or commerce). This research aims to find out the practice of giving wages for keeping cattle and what the perspective of sharia business law is on giving these wages. The research method uses empirical juridical, using a conceptual approach and analyzed using inductive and descriptive methods. The data collection techniques used were observation, interviews, documentation and library data. The results of the research concluded that the provisions for providing wages for keeping cattle in Beji Jogoroto hamlet are not in accordance with the provisions of sharia business law, namely wages given to cattle keepers who have carried out their work, these wages are not in accordance with the results of the agreement at the beginning of the contract, and here the keeper must Ridho accepts the wages given by the cow owner.